MINDSET MUTU MANAJEMEN PERGURUAN TINGGI ISLAM DALAM PROGRAM MERDEKA BELAJAR KAMPUS MERDEKA (MBKM) - Denny Kodrat (STAI Sebelas April Sumedang, 2021)
Freedom to learn, independent campus (MBKM) is one of distinguished program of Ministry of Education and Culture. In the program, it is expected that students improve their soft skills and hard skills by joining one of eight programs offered by the university. Link and Match was an initial program released in 1990s and then has been revised by the MBKM program. This manuscripts is aimed at revealing the important of quality mindset in Islamic higher school management in running the program. Some library researches and references are presented to enrich the analysis including reputable journals and books. The concept of a critical education is used as a tool of analysis. The theory of education suggested by Illich (2000), Walker (1981), dan Nabhani (2001) is used while the concept of Total Quality Management (TQM) in education stated by Salis (2002) is carried as a framework of analysis in discussing the study. The study shows that quality mindset plays an important role in maintaining the Islamic higher school existence in the middle of change and government demand, industry and factory world, and encourage Islamic university in competition with other campuses in Indonesia.